2022
DOI: 10.3390/act11110337
|View full text |Cite
|
Sign up to set email alerts
|

PSO-Based Variable Parameter Linear Quadratic Regulator for Articulated Vehicles Snaking Oscillation Yaw Motion Control

Abstract: In this paper, the seven degrees of freedom (DOF) nonlinear system model of articulated vehicles, including the vehicle dynamics model, tire and hydraulic steering system model, and the linearized ideal reference model, is constructed. A layered stability controller for the articulated vehicle is built. The particle swarm optimization (PSO)-based variable parameter linear quadratic regulator (LQR) for the upper-level yaw torque controller and the lower-level torque distributor based on the principle of the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, at the same time, there is a problem related to the maneuverability and stability of such vehicles [5,17,18]. For example, in the paper [2,6,8] it was shown that for trailed road trains, the interconnections between individual links can generate a specific oscillating trailers behavior during vehicle maneuvers. This is confirmed by the paper results [1], where it is noted that trailed road trains with a large number of trailers exhibit unstable driving modes at high speeds, including folding links, trailer rolling and rollover.…”
Section: Methodsmentioning
confidence: 99%
“…However, at the same time, there is a problem related to the maneuverability and stability of such vehicles [5,17,18]. For example, in the paper [2,6,8] it was shown that for trailed road trains, the interconnections between individual links can generate a specific oscillating trailers behavior during vehicle maneuvers. This is confirmed by the paper results [1], where it is noted that trailed road trains with a large number of trailers exhibit unstable driving modes at high speeds, including folding links, trailer rolling and rollover.…”
Section: Methodsmentioning
confidence: 99%
“…Although the LQR is widely employed in vehicle control, there remains an issue concerning empirical parameter conditions. Therefore, in order to effectively control serpentine oscillation, Lei et al [ 20 ] used the Particle Swarm Optimization (PSO) algorithm to optimize LQR parameters. Wang et al [ 21 ] proposed a gain scheduling robust linear-quadratic regulator (RLQR) that addressed the limitations of parameter uncertainty by adding an additional control term to the feedback contribution of the conventional LQR.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have shown promising results in enhancing the LQR algorithm, there is still potential for further improvement in terms of control accuracy and stability. Lei et al [29] improved the effectiveness of the articulated vehicle winding oscillation controller by optimizing each parameter in the LQR controller through Particle Swarm Optimization (PSO). The GA-PSO algorithm combines the advantages of the GA and PSO and demonstrates strong performance in solving complex optimization problems.…”
Section: Introductionmentioning
confidence: 99%